Analysis of Chemical Properties and Soil Fertility Status in Paddy Fields in Sakti Sub-district, Pidie Regency, Aceh - Magfirah, Dhiya; Zuraida, Zuraida; Sufardi, Sufardi (Department of Agricultural Engineering, Syiah Kuala University, 2024)
Abstract. This research aims to evaluate the chemical properties of soil and the status of soil fertility in rice fields in Sakti Sub-district, Pidie Regency, Aceh. This research uses quantitative descriptive methods through field observations and soil analysis in the laboratory. The area of rice fields evaluated was 2,331 hectares with a total of eight observation points at a depth of 0-20 cm. Four sub-samples were taken from each observation point and then composited. Soil chemical indicators analyzed as parameters to assess soil fertility status include cation exchange capacity (CEC), base saturation (KB), Organic C, and total P2O5 and K2O content of 25% HCl extract. The research results showed that soil chemical characteristics, namely pH H2O, CEC, BS, as well as soil P2O5 and K2O potential varied between sample locations. In general, rice fields in Sakti Sub-district, Pidie Regency have acid to neutral soil pH (5.51-7.00), very low to moderate organic C (0.46-2.26%), medium to high CEC (22, 8-44.4 cmol kg-1), and low to high BS (35.4-53.3%). Total P2O5 of soils at all locations was classified as very high (64.4-169.28 mg/100 g), while total K2O varied from low to high (18.72-44.76 mg/100 g). The soil fertility status in the rice fields of Sakti Sub-district has two criteria, namely low and medium. To improve soil fertility status, this can be done by using local straws from harvest residuesAnalisis Sifat Kimia dan Status Kesuburan Tanah pada Lahan sawah di Kecamatan Sakti Kabupaten Pidie, Provinsi AcehAbstrak. Evaluasi sifat kimia dan status unsur hara sangat penting untuk menjaga agar kondisi lahan sawah tetap mendukung produksi. Penelitian ini bertujuan untuk evaluasi sifat kimia serta status kesuburan taanah pada lahan sawah di Kecamatan Sakti Kabupaten Pidie, Provinsi Aceh. Penelitian ini menggunakan metode deskriptif kuantitatif melalui pengamatan di lapangan dan analisis tanah di laboratorium. Luas areal sawah yang dievaluasi adalah 2.331 hektar dengan jumlah titik pengamatan ada delapan titik pada kedalaman 0-20 cm. Setiap titik pengamatan diambil sebanyak empat sub-sampel kemudian dikompositkan. Indikator kimia tanah yang dianalisis sebagai parameter untuk menilai status kesuburan tanah antara lain: kapasitas tukar kation (KTK), kejenuhan basa (KB), C Organik, dan kandungan total P2O5 dan K2O total ekstrak HCl 25%. Hasil penelitian menunjukkan bahwa karakteristik kimia tanah yaitu pH H2O, KTK, KB, serta cadangan P2O5 dan K2O tanah bervariasi antara lokasi sampel. Secara umum lahan sawah di Kecamatan Sakti Kabupaten Pidie mempunyai pH tanah masam hingga netral (5,51-7,00), C-organik sangat rendah hingga sedang (0,46-2,26%), KTK sedang hingga tinggi (22,8-44,4 cmol kg-1), dan KB rendah hingga tinggi (35,4-53,3%). Cadangan P2O5 tanah di seluruh lokasi tergolong sangat tinggi (64,4-169,28 mg/100 g), sedangkan cadangan K2O bervariasi dari rendah hingga tinggi (18,72-44,76 mg/100 g). Status kesuburan tanah di areal sawah Kecamatan Sakti memiliki dua kriteria yaitu rendah dan sedang. Untuk meningkatkan status kesuburan tanah, dapat dilakukan dengan pemanfaatan jerami setempat dari sisa panen.